Activating Boxmind: an evaluation of a Web-based video lecture with synchronized activities - Richard Joiner; Catherine Durkin; Derek Morrison; Lisa Williams (Association for Learning Technology, 2003)
The aim of this study was to evaluate the use of synchronous computer-mediated communication activities in a video e-lecture. Previous research has reported that learning is facilitated when communication activities are added to a video lecture. Twelve postgraduate students participated in the study and they viewed a video e-lecture on the perspective-taking theory of communication. The lecture consisted of a video image of the lecturer, an audio track, slides, the transcript and a number of communication activities. They were given a pre-test a week before the lecture and a post-test a week after. They were also asked to rate the helpfulness of various aspects of the lecture. Students' post-test scores were statistically significantly higher than their pre-test scores. They found the audio track, transcript, slides and activities helpful. The most helpful aspects were the communication activities. The implications of these findings are discussed.